Oral Immunisation With Non‐GMO Surface Displayed SARS‐CoV‐2 Spike Epitopes on Bacteria‐Like Particles Provokes Robust Humoral and Cellular Immune Responses, and Modulated the Gut Microbiome in Mice - Robie Vasquez; Ji Hoon Song; Remilyn M. Mendoza; In‐Chan Hwang; Bernadette B. Bagon; Lars Engstrand; Valerie Diane Valeriano; Dae‐Kyung Kang (Microbial Biotechnology)
ABSTRACT The coronavirus disease 2019 (COVID‐19) is a fatal disease caused by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). To date, several vaccines have been developed to combat the spread of this virus. Mucosal vaccines using food‐grade bacteria, such as Lactobacillus spp., are promising strategies for developing safe and effective vaccines against SARS‐CoV‐2. In this study, we designed a non‐GMO surface‐displayed SARS‐CoV‐2 spike S1 epitope on Limosilactobacillus fermentum‐derived bacteria‐like particles (BLPs). After that, we evaluated its efficacy to induce immune responses in immunocompetent mice. Moreover, we examined the influence of oral immunisation on the gut microbiome and microbiota metabolites. Twenty‐eight 6‐week‐old male C57BL/6 mice were orally immunised with the following: PBS (control), Lm. fermentum‐derived BLPs only, BLPs displaying SARS‐CoV‐2 spike S1‐2, or BLPs displaying SARS‐CoV‐2 spike S1‐3 epitopes. Our results showed that mucosal immunisation of mice with surface‐displayed SARS‐CoV‐2 spike epitopes provoked high‐level secretory IgA and systemic IgG production. Moreover, the immunisation exhibited a Th1‐like immune response, characterised by an elevated IgG2a‐to‐IgG1 ratio and high antiviral IFN‐γ production. In addition, we observed gut microbiome modulation and increased butyrate production in immunised mice. Overall, the use of Lm. fermentum‐derived BLPs and the anchor CshA to display SARS‐CoV‐2 spike S1epitopes is a promising novel strategy in developing a cost‐effective, non‐GMO mucosal vaccine alternative against SARS‐CoV‐2.